Caracterização de um dispositivo de cristal líquido para implementação de operações programáveis sobre o estado de polarização da luz - Erick Ribeiro de Carvalho (2024)
Liquid crystal displays (LCDs) are devices capable of manipulating properties of an incident light beam, such as amplitude, phase, and polarization, based on the voltage applied to their molecules. In this work, we will experimentally characterize the effect of an LCD on light polarization, aiming at its use as a programmable spatial light modulator (SLM) in optics and quantum information experiments. In the first part, we will determine the Mueller matrix of the device and, from it, its polarimetric properties. We will show that the LCD acts only approximately as an ideal retarder plate since it introduces depolarization to the incident light. In the second part, we investigate the behavior of the LCD through the formalism of quantum operations, treating its action as an operation on polarization qubit states. Through process tomography, we determine the matrix characterizing the device's operation and show that it is non-unitary. Next, we derive a general expression for the process matrix of an SLM, given by the combination of the LCD with wave plates. This expression will allow us to implement programmable operations on the polarization states of light based on the configuration of the wave plates and the voltage on the LCD. As an application, we will quantify the fidelity of the actual operation implemented by the SLM with an ideal unitary operation of interest in quantum information protocols.